EPEN-07. SINGLE-CELL RNA SEQUENCING IDENTIFIES A UNIQUE MYELOID SUBPOPULATION ASSOCIATED WITH MESENCHYMAL TUMOR SUBPOPULATION IN POOR OUTCOME PEDIATRIC EPENDYMOMA. (1st June 2021) - Griesinger, Andrea; Riemondy, Kent; Donson, Andrew; Willard, Nicholas; Prince, Eric; Harris, Faith; Amani, Vladimir; Grimaldo, Enrique; Hankinson, Todd; Grundy, Richard; Jackson, Andrew; Foreman, Nicholas; et al.
Abstract: We have previously shown immune gene phenotype variations between posterior fossa ependymoma subgroups. PFA1 tumors chronically secrete IL-6, which induces secretion of myeloid cell IL-8 and pushes the infiltrating myeloid cells to an immune suppressive function. In contrast, PFA2 tumors have a more immune activated phenotype associated with a better prognosis. The objective of this study was to use single-cell(sc) RNAseq to descriptively characterize the infiltrating myeloid cells. We analyzed approximately 8500 cells from 21 PFA patient samples. Using advanced machine learning, we identified eight myeloid cell subpopulations with unique gene expression profiles. Interestingly, only one subpopulation was significantly enriched in PFA1 tumors. This subpopulation, denoted as the hypoxia myeloid subpopulation, was defined by genes associated with angiogenesis, response to hypoxia, wound healing, cell migration, neutrophil activation and response to oxygen levels. These myeloid cells also share similar gene expression profile to a mesenchymal tumor subpopulation (MEC) enriched in PFA1 and associated with poor outcome in EPN patients. This tumor subpopulation was the only population expressing IL-6. Using immunohistochemistry, we found the hypoxia myeloid located in regions of tumor necrosis and perivascular niches. The MEC cells were also more abundant in these regions. In an independent single-cell cytokine release assay, we identified eight subpopulations of functional myeloid cells. One subpopulation significantly secreted IL-8, which represented the hypoxia subpopulation based on IL-8 gene expression in the scRNAseq dataset. This data suggests the tumor necrosis resulting in the development of MEC tumor subpopulation is driving the immune suppressive myeloid phenotype in PFA1 tumors through polarization of myeloid cells to the hypoxia subpopulation. Further studies are needed to determine how these myeloid cells interact with the lymphocyte subpopulations and whether they contribute to the progression of PFA1 EPN.